2005
DOI: 10.1158/0008-5472.can-05-2632
|View full text |Cite
|
Sign up to set email alerts
|

Activated B-RAF Is an Hsp90 Client Protein That Is Targeted by the Anticancer Drug 17-Allylamino-17-Demethoxygeldanamycin

Abstract: Hsp90 is a ubiquitously expressed molecular chaperone that folds, stabilizes, and functionally regulates many cellular proteins. The benzoquinone ansamysin 17-allylamino-17-demethoxygeldanamycin (17-AAG) is an anticancer drug that disrupts Hsp90 binding to its clients, causing their degradation through the ubiquitin-dependent proteasomal pathway. The protein kinase B-RAF is mutated in f7% of human cancers. The most common mutation (f90%) is V600E B-RAF, which has constitutively elevated kinase activity, stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
208
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 236 publications
(227 citation statements)
references
References 18 publications
16
208
2
1
Order By: Relevance
“…We found that the interaction of either cdc2 or cdc25c with p50 cdc37 decreased after GA treatment ( Figure 6) and that conversely, the association of cdc2 and cdc25c with Hsp70 in glioblastoma cells increased over time after GA treatment ( Figure 6). We conclude from these experiments that cdc2 and cdc25c are Hsp90 client proteins and that ansamycin treatment alters the composition of the chaperone complexes associated with either cdc2 or cdc25c, as it has been demonstrated with oncoproteins such as bcr-abl, src , Akt , or mutated B-raf (da Rocha et al, 2005;Grbovic et al, 2006). After GA treatment, the multichaperone complex tends to adopt the ADP-bound conformation, which may target cdc2 and cdc25c proteins for degradation, presumably via the proteasome.…”
Section: Discussionmentioning
confidence: 61%
“…We found that the interaction of either cdc2 or cdc25c with p50 cdc37 decreased after GA treatment ( Figure 6) and that conversely, the association of cdc2 and cdc25c with Hsp70 in glioblastoma cells increased over time after GA treatment ( Figure 6). We conclude from these experiments that cdc2 and cdc25c are Hsp90 client proteins and that ansamycin treatment alters the composition of the chaperone complexes associated with either cdc2 or cdc25c, as it has been demonstrated with oncoproteins such as bcr-abl, src , Akt , or mutated B-raf (da Rocha et al, 2005;Grbovic et al, 2006). After GA treatment, the multichaperone complex tends to adopt the ADP-bound conformation, which may target cdc2 and cdc25c proteins for degradation, presumably via the proteasome.…”
Section: Discussionmentioning
confidence: 61%
“…Antibodies used are listed in Supplementary Materials. 5 Cell Cycle Analysis Cell cycle effects were determined using propidium iodide staining and flow cytometry (36).…”
Section: Methodsmentioning
confidence: 99%
“…Control, plasma, and tumor (100 AL) were analyzed for compound levels following protein precipitation with 5 Supplementary materials for this article are available at Molecular Cancer Therapeutics Online (http://mct.aacrjournals.org/). 3 volumes of methanol containing an analogue as internal standard.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that, in human melanocyte-derived cells, SCF is as strong an activator of the PI3K pathway as in murine melanocytes. In 501mel cells, the Erk pathway is constitutively activated by a B-Raf mutation (da Rocha Dias et al, 2005) and insensitive to SCF. To confirm these results in vivo, we examined c-Kit expression and Akt phosphorylation in situ using immunohistochemistry c-KIT mutants are oncogenic in melanocytes G Monsel et al in an acral tumor containing the D576 c-Kit mutation.…”
Section: D576pmentioning
confidence: 99%